2011
DOI: 10.1016/j.jchemneu.2011.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptors stimulate brain region specific metabotropic glutamate receptors to rapidly initiate signal transduction pathways

Abstract: Estradiol and other steroid hormones modulate the nervous system and behavior on both acute and long-term time scales. Though estradiol was originally characterized as a regulator of gene expression through the action of nuclear estrogen receptors (ER) that directly bind DNA to regulate gene expression, research over the past thirty years has firmly established that estradiol can initiate signaling pathways via extra-nuclear ERs associated with the cellular membrane, producing changes in neurons through stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
92
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 115 publications
(95 citation statements)
references
References 61 publications
3
92
0
Order By: Relevance
“…Although G␣ i ␤␥ mediates the ER␣-induced neuroprotective effect ), a G q -mediated signaling has also been linked to membrane ER␣ activation in astrocytes (Chaban et al, 2004). Our data, however, support the hypothesis that membrane ERs are not themselves G protein-coupled receptors but rather use mGlu1 receptor to signal, as previously suggested Meitzen and Mermelstein, 2011). MAPK signaling is known to participate in the neuroprotective effect of estrogen.…”
Section: Interaction Of Er␣ and Mglu1 Receptors In Neuroprotection 17supporting
confidence: 75%
“…Although G␣ i ␤␥ mediates the ER␣-induced neuroprotective effect ), a G q -mediated signaling has also been linked to membrane ER␣ activation in astrocytes (Chaban et al, 2004). Our data, however, support the hypothesis that membrane ERs are not themselves G protein-coupled receptors but rather use mGlu1 receptor to signal, as previously suggested Meitzen and Mermelstein, 2011). MAPK signaling is known to participate in the neuroprotective effect of estrogen.…”
Section: Interaction Of Er␣ and Mglu1 Receptors In Neuroprotection 17supporting
confidence: 75%
“…This interaction between ER␣ and mGluR1a has been shown to be important for the control of both female sexual receptivity and the release of neuroprogesterone from astrocytes in the hypothalamus (for review, see Micevych and Mermelstein, 2008;Micevych et al, 2009). In fact, recent work has shown that ERs may be able to interact with several different kinds of mGluRs in brain-region-specific patterns to activate many G-protein-coupled signaling cascades (Meitzen and Mermelstein, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, dorsal hippocampal infusion of BSA-E 2 in adult ovariectomized mice induces a similar ERK-dependent enhancement of object recognition memory consolidation to that observed after dorsal hippocampal infusion of free E 2 (Fernandez et al 2008), suggesting that membrane ERs mediate the memory-enhancing effect of E 2 by activating ERK signaling. Data such as these have led to a general acceptance that a membrane-associated ER facilitates the rapid nonclassical effects of E 2 (e.g., Micevych and Dominguez 2009) and have prompted some investigators to suggest that BSA-E 2 binds to ERa and ERb localized within the membrane (Meitzen and Mermelstein 2011). Although one provocative report indicates that ERa in the hypothalamus has an extracellular domain and can be internalized by E 2 and mGluR1a ligands (Bondar et al 2009), it is not yet widely accepted that ERa is an integral membrane protein.…”
Section: Estrogen Receptor Localization and Mechanism Of Action Era Amentioning
confidence: 99%